Characterization of spermatheca-related genes in Aedes aegypti - Pascini, Tales Vicari (2018)
Aedes aegypti is an important hematophagous mosquito, with anthropophilic habits, also known as vector of important pathogens to humans, such as Yellow Fever, Dengue, Chikungunya, and, Zika viruses. A. aegypti females usually mate once, receiving the sperm to produce the whole offspring during their reproductive period. The spermatheca is responsible for sperm maintenance, nutrition and protection against physical and oxidative stress damage leading the long-term sperm storage process, resulting in the increase of the female fecundity. This reproductive autonomy of the females enhances their dispersion and then their vectorial capacity and the spermatheca play pivotal role providing the suitable environment, guaranteeing the sperm viability. There are three spermathecae in A. aegypti: two lateral and a central larger one. Considering the importance of this organ, in the present work, we reviewed different aspects of the spermatheca of insects, highlighting its importance for the reproductive success of the insects. This review also highlighted the number of spermathecae according to different taxonomic group, the role of different spermathecal parts (duct, reservoir, and gland), emphasizing their function along the processes of sperm maintenance. We also aimed to elucidate that the global gene expression in virgin and fertilized spermathecae (“spermathecomes”) separately, through RNA sequencing and bioinformatics analyzes. In virgin females, there is a greater number of coding sequences related to the establishment environment to receive and to allocate the spermatozoa. In fertilized spermathecae the most representative transcripts are related to the maintenance of the spermathecal microenvironment, thus prolonging the viability of these gametes. Differentially expressed genes (DEGs) were also analyzed by comparing virgin and fertilized spermathecae. We attempted the silencing of some of these DEG by the RNAi technique, to analyze the effects of knocking-down these genes throughout the reproductive process in A. aegypti. The females were injected with dsRNA of eight different genes related to energy metabolism (Ae-92048), chitin-bound components (Ae- 187521 and Ae-88956), transcriptional regulation (Ae-27176), hormonal regulation (AeSigP- 4002), enzymatic activity (Ae-SigP-212177), antimicrobial activity (AeSigP-109183) and ion homeostasis (AeSigP-66427). The gene silencing decreased the female survival, reduced the blood-feeding intake, nutrients storage/conversion, egg production and oviposition and offspring productions. In addition, the silencing of AeSigP-66427 affecting sperm motility and impaired egg production. At last, by the in situ hybridization we could detect in which part or the spermatheca, the chosen target genes are expressed. The present work is pioneer to identify the collection of genes expressed the virgin and fertilized spermathecae of A. aegypti. Through this intriguing study, we were able to elucidate the genes and some processes related to the long-term storage of spermatozoa in A. aegypti. Moreover, this work provided the basis for the establishment of alternative strategies to control this vector, by reducing its reproductive capacity.